The SAGE handbook of sports economics - Downward, Paul, 1964- (SAGE Publications, 2019)
Sports economics is a well-established and dynamic area of study; a key component in the fields of sport management, sport science and sport studies, as well as in other areas of economics, finance and management. Covering amateur to professional sports, individual events and organised tournaments, this Handbook provides an authoritative contribution to the understanding of sport in the economy. The editors of The SAGE Handbook of Sports Economics have brought together a global team of respected scholars to create this benchmark collection of insights into sports economics. Each chapter includes a study of a specific context in which issues arise in sports economics, a critical presentation of its main theoretical contributions, an overview of current research findings, and an outline of enquiry for future research. PART I: The Nature and Value of the Sports System and Economy PART II: Amateur Sports Participation, Supply and Impact PART III: Professional Team Sports PART IV: Professional Sports Leagues PART V: Sports Events and their Impacts PART VI: Individual Sports PART VII: Future Research- Resumé vydavatel
Keywords: ekonomika sportu; sporty -- ekonomické aspekty; sports economics -- economic aspects; sports; elektronické knihy; příručky; electronic books; handbooks and manuals